Trastuzumab Modified Barium Ferrite Magnetic Nanoparticles Labeled with Radium-223: A New Potential Radiobioconjugate for Alpha Radioimmunotherapy - Weronika Gawęda; Marek Pruszyński; Edyta Cędrowska; Magdalena Rodak; Agnieszka Majkowska-Pilip; Damian Gaweł; Frank Bruchertseifer; Alfred Morgenstern; Aleksander Bilewicz (Nanomaterials, 2020)
Barium ferrite nanoparticles (BaFeNPs) were investigated as vehicles for 223Ra radionuclide in targeted α-therapy. BaFe nanoparticles were labeled using a hydrothermal Ba2+ cations replacement by 223Ra with yield reaching 61.3 ± 1.8%. Radiolabeled nanoparticles were functionalized with 3-phosphonopropionic acid (CEPA) linker followed by covalent conjugation to trastuzumab (Herceptin®). Thermogravimetric analysis and radiometric method with the use of [131I]-labeled trastuzumab revealed that on average 19–21 molecules of trastuzumab are attached to the surface of one BaFe–CEPA nanoparticle. The hydrodynamic diameter of BaFe–CEPA–trastuzumab conjugate is 99.9 ± 3.0 nm in water and increases to 218.3 ± 3.7 nm in PBS buffer, and the zeta potential varies from +27.2 ± 0.7 mV in water to −8.8 ± 0.7 in PBS buffer. The [223Ra]BaFe–CEPA–trastuzumab radiobioconjugate almost quantitatively retained 223Ra (>98%) and about 96% of 211Bi and 94% of 211Pb over 30 days. The obtained radiobioconjugate exhibited high affinity, cell internalization and cytotoxicity towards the human ovarian adenocarcinoma SKOV-3 cells overexpressing HER2 receptor. Confocal studies indicated that [223Ra]BaFe–CEPA–trastuzumab was located in peri-nuclear space. High cytotoxicity of the [223Ra]BaFe–CEPA–trastuzumab bioconjugate was confirmed by radiotoxicity studies on SKOV-3 cell monolayers and 3D-spheroids. In addition, the magnetic properties of the radiobioconjugate should allow for its use in guide drug delivery driven by magnetic field gradient.